2022
DOI: 10.3390/metabo12030220
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Plasma Lipid Levels Following Cortical Spreading Depolarization in a Transgenic Mouse Model of Familial Hemiplegic Migraine

Abstract: Metabolite levels in peripheral body fluids can correlate with attack features in migraine patients, which underscores the potential of plasma metabolites as possible disease biomarkers. Migraine headache can be preceded by an aura that is caused by cortical spreading depolarization (CSD), a transient wave of neuroglial depolarization. We previously identified plasma amino acid changes after CSD in familial hemiplegic migraine type 1 (FHM1) mutant mice that exhibit increased neuronal excitability and various m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…and without aura, with associations with disease duration [37][38][39] • Hypoglycaemia reduced CSD threshold, increased duration and exhibited spontaneous CSD events [29][30][31] Repeated migraine attacks and activation of nociceptive regions may lead to abnormalities in glucose metabolism Lactate production • Serum and plasma measurements exhibit upregulated lactate in migraine patients both with and without aura [44][45][46] • 1 H-MRS studies demonstrated increased lactate in familial hemiplegic migraine and migraine with aura, but not in migraine without aura [48][49][50] • Rat 1 H-MRS studies exhibit increased lactate and reduced pH during CSD [41] Lactate excess may be produced as a result of tissue hypoxia during metabolically challenging events such as CSD. Lactate may be used as alternative energy substrate and could signify an impaired astrocytic-neuronal interaction Lipid metabolism • Alterations cholesterol and LDL were identified in migraine patients [58][59][60][61] • Higher lipid content in serum was associated with frequency and severity of migraine attacks [59,60,62] Following CSD in mice, blood metabolite measurements exhibit alterations in lipid metabolism including increased prostaglandin and anti-inflammatory lipid mediators [66] It is unknown if hyperlipemia is a cause or effect of migraine or related to comorbidities. Associations with cholesterol and LDL may provide an explanation for the increased cardiovascular and stroke risk in migraine with aura [63,64] Fatty acid oxidation • Chronic migraine patients demonstrated differentially metabolized fatty acids compared to controls, with levels correlating with depression [76] • PEA supplementation reduced headache attacks per month and pain intensity in migraine without aura, [78] and reduced pain intensity (in combination with non-steroidal anti-inflammatory analgesics) in migraine with aura [79].…”
Section: Glucose Utilization • Glucose Hypometabolism In Migraine Pat...mentioning
confidence: 99%
See 1 more Smart Citation
“…and without aura, with associations with disease duration [37][38][39] • Hypoglycaemia reduced CSD threshold, increased duration and exhibited spontaneous CSD events [29][30][31] Repeated migraine attacks and activation of nociceptive regions may lead to abnormalities in glucose metabolism Lactate production • Serum and plasma measurements exhibit upregulated lactate in migraine patients both with and without aura [44][45][46] • 1 H-MRS studies demonstrated increased lactate in familial hemiplegic migraine and migraine with aura, but not in migraine without aura [48][49][50] • Rat 1 H-MRS studies exhibit increased lactate and reduced pH during CSD [41] Lactate excess may be produced as a result of tissue hypoxia during metabolically challenging events such as CSD. Lactate may be used as alternative energy substrate and could signify an impaired astrocytic-neuronal interaction Lipid metabolism • Alterations cholesterol and LDL were identified in migraine patients [58][59][60][61] • Higher lipid content in serum was associated with frequency and severity of migraine attacks [59,60,62] Following CSD in mice, blood metabolite measurements exhibit alterations in lipid metabolism including increased prostaglandin and anti-inflammatory lipid mediators [66] It is unknown if hyperlipemia is a cause or effect of migraine or related to comorbidities. Associations with cholesterol and LDL may provide an explanation for the increased cardiovascular and stroke risk in migraine with aura [63,64] Fatty acid oxidation • Chronic migraine patients demonstrated differentially metabolized fatty acids compared to controls, with levels correlating with depression [76] • PEA supplementation reduced headache attacks per month and pain intensity in migraine without aura, [78] and reduced pain intensity (in combination with non-steroidal anti-inflammatory analgesics) in migraine with aura [79].…”
Section: Glucose Utilization • Glucose Hypometabolism In Migraine Pat...mentioning
confidence: 99%
“…It is not yet known if increased cholesterol in migraine is a cause, an effect or correlations are due to underlying common factors. However, metabolite measurements in blood from mice following CSD also demonstrate alterations in lipid metabolism including increased prostaglandin and anti-inflammatory lipid mediators [66]. Additional studies in murine model are needed to further elucidate links between migraine, aura subtypes and cholesterol metabolism as well as pathophysiology.…”
Section: Lipid Metabolism: Cholesterolmentioning
confidence: 99%